2016
DOI: 10.1063/1.4941313
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive non-collinear autocorrelation of few-cycle pulses with an angular tunable bi-mirror

Abstract: Adaptive autocorrelation with an angular tunable micro-electro-mechanical system is reported. A piezo-actuated Fresnel bi-mirror structure was applied to measure the second order autocorrelation of near-infrared few-cycle laser pulses in a non-collinear setup at tunable superposition angles. Because of enabling measurements with variable scaling and minimizing the influence of distortions by adaptive self-reconstruction, the approach extends the capability of autocorrelators. Flexible scaling and robustness ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is worth mentioning that the autocorrelation signal, defined by (3) or (4), is ideally an even function of regardless of the symmetry of the actual pulse. Furthermore, the ratio between the maximum value and the background level for the interferometric and intensity autocorrelation signals is 8 to 1 and 3 to 1, respectively [11].…”
Section: Theoretical Background and Device Descriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is worth mentioning that the autocorrelation signal, defined by (3) or (4), is ideally an even function of regardless of the symmetry of the actual pulse. Furthermore, the ratio between the maximum value and the background level for the interferometric and intensity autocorrelation signals is 8 to 1 and 3 to 1, respectively [11].…”
Section: Theoretical Background and Device Descriptionmentioning
confidence: 95%
“…Another technique that requires high spatial coherence for few-cycle pulses measurement using an angular tunable bi-mirror for noncollinear autocorrelation is reported in ref. [11].…”
Section: Introductionmentioning
confidence: 99%
“…As an application of combined SLM and Fresnel bi-mirror (configuration Com 1), we studied the possibility to improve the quality of non-collinear autocorrelation of few-cycle pulses. The principle of adaptive non-collinear autocorrelation with flexible Fresnel bi-mirrors was previously published by some of the authors [52]. Arrangement and signal analysis are described in this reference.…”
Section: Contrast Management For Non-collinear Autocorrelationmentioning
confidence: 99%
“…Diffraction at the edges can mostly be eliminated. Information about second-order field autocorrelation can be derived from averaged horizontal cuts through the intensity profiles [52].…”
Section: Contrast Management For Non-collinear Autocorrelationmentioning
confidence: 99%
“…Fresnel mirrors can, for example, be used to fabricate linear optical gratings directly into the photoresist without the use of a photomask [3]. It was shown that an adaptive Fresnel mirror can be used in adaptive pulse autocorrelation [4], and for direct nano-machining of subwavelength structures on silicon or dielectric substrates by laser-induced periodic surface structures (LIPSS) [5,6]. LIPSS are formed by the interference of incident and scattered light pulses on the surface of the material [7].…”
Section: Introductionmentioning
confidence: 99%